2018
DOI: 10.3892/mmr.2018.9473
|View full text |Cite
|
Sign up to set email alerts
|

Association between the methylation of six apoptosis‑associated genes with autism spectrum disorder

Abstract: Excessive apoptosis hinders the process of brain maturation and is regarded as one of the principal risk factors for the development of autism spectrum disorder (ASD). The aim of the present study was to investigate the association between the methylation of six apoptosis‑associated genes [transforming growth factor β 1 (TGFB1), BCL2 associated X, apoptosis regulator, insulin like growth factor binding protein 3, protein kinase C β 1, presenilin 2 and C‑C motif chemokine ligand 2] and ASD. Using quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In addition to disease severity, peripheral blood DNA methylation has been associated with the behavioral phenotypes of ASD. Indeed, the methylation of a CpG site of the ST8SIA2 gene has been found to positively correlate with stereotyped behaviors [49], while the methylation of TGFB1 was found to positively correlate with the interaction ability score [50]. Although the results of these studies are of great interest, as they suggest that peripheral DNA methylation could provide biomarkers to detect different levels of expression of the ASD spectrum, they need to be replicated in further studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to disease severity, peripheral blood DNA methylation has been associated with the behavioral phenotypes of ASD. Indeed, the methylation of a CpG site of the ST8SIA2 gene has been found to positively correlate with stereotyped behaviors [49], while the methylation of TGFB1 was found to positively correlate with the interaction ability score [50]. Although the results of these studies are of great interest, as they suggest that peripheral DNA methylation could provide biomarkers to detect different levels of expression of the ASD spectrum, they need to be replicated in further studies.…”
Section: Discussionmentioning
confidence: 96%
“…In that study, a higher frequency of OXTR promoter hypomethylation was observed in the peripheral blood of 27 ASD individuals compared to 39 TD individuals [37]. The qMSP technique was used in two studies [42,50]. Hu et al investigated methylation levels of the HTR4 gene in the peripheral blood of 61 ASD children and 66 TD children, and decreased methylation was observed in the ASD individuals.…”
Section: Main Dna Methylation Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three isoforms are expressed in several central nervous system CNS cell types including neurons, astrocytes, and microglia [3]. In the past, it has been observed that the expression level of TGFB1 in the plasma of autistic children is significantly reduced [23]. The MAPK pathway regulates neural progenitor biogenesis, learning and memory, and mRNA translation by phosphorylation of TSC2 and eIF4E through MAPK-interacting kinase 1 and 2 (MNK1 and MNK2).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, dentre os seis genes associados à apoptose, a sinalização do TGFB1 pode ser comprometida no TEA, por meio de uma hipometilação significativa, tendo assim uma consequência cognitiva secundária associada ao transtorno (ZHAO et al, 2018). Não somente a hipometilação, mas também a hipermetilação pode contribuir para deficiências cognitivas, como a hipermetilação nas regiões promotoras de codificação (ilhas CpG do tipo 16) sendo possível causa de déficits mais pronunciados na teoria da mente e na autoconsciência.…”
Section: Domínio Cognitivounclassified